Management of biologics in oral surgery - Mills Sophie; Ryan Patrick; Gaffney Karl (EDP Sciences, 2023)
Biologics have revolutionised the management of immune-mediated inflammatory disorders, and their growing use has resulted in increasing numbers of these patients presenting in oral surgery settings. While the efficacy of biologics has been well established, they are associated with numerous adverse effects. Several professional bodies have published recommendations on perioperative management of these agents to reduce complications. Currently no specific dental or oral surgery guidance exists. The aim of this paper is to review the current literature and guidance regarding the use of biologics in the perioperative period.